HUMAN RESOURCES OPTIMIZATION AND UTILIZATION OF ACCRUAL BASED ACCOUNTING INFORMATION TECHNOLOGY ON PERFORMANCE OF SURAKARTA CITY GOVERNMENT FINANCIAL REPORTING - Addina Hapsari; Siti Nurlaela; Kartika Hendra Titisari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2019)
This research is conducted by explaining about two research variables, namely Optimization of Human Resources and Utilization of Accrual-Based Accounting Information Technology has a positive influence on Financial Reporting Performance. The research sample was employees of the Badan Pendapatan, Pengelolaan, Keuangan, dan Aset Daerah (BPPKAD). Data collection is done by taking 35 respondents from BPPKAD employees using questionnaires as research instruments. The sampling technique uses a purposive / judgment sampling method which was developed from the results of research by Umar Sekaran (2006).IITheIIresultsIIofIItheIIstudy show that H1 research has aIIIpositiveIIIinfluence on the financial statement performance variables, as well as H2 which has a positive influence on the performance of financial statements. In the F test shows the results that the two variables have a simultaneous influence on Y. Keywords: optimization, human resources, utilization, accrual based accounting system, accounting information system.